The gender lifetime earnings gap: Exploring gendered pay from the life course perspective - Christina Boll; Malte Jahn; Andreas Lagemann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2017)
Research on the gender earnings divide so far mostly focuses on the gender gap in hourly wages which, due to its snapshot nature, is inappropriate to capture the biographical dimension of gendered pay. With the 'gender lifetime earnings gap' (GLEG), we introduce a new measure that meets this requirement. Based on a group of 93,511 German individuals born 1950-64 from the 'Sample of Integrated Labour Market Biographies' (SIAB 7510), we find that at the end of the employment career, women accumulated 49.8 % less earnings than men. Thus, the GLEG is more than twice as high as the current German gender pay gap. The GLEG is the largest (smallest) at the bottom (top) of the earnings distribution. It most prominently widens during the period of family formation (age 25-35). Relatedly, gender differences in endowments, mainly in terms of experience and hours, answer for three quarters of the GLEG. For younger cohorts, family breaks tend to lose importance whereas the role of work hours remains unchanged. Furthermore, the GLEG notably differs between occupational segments.
Keywords: D31; J31; J16; 330; lifetime earnings; Blinder & Oaxaca decomposition; occupational segments; cohort analysis; gender; life course; wage distribution; wage gap